The Role of UPTD BLK Bali Industry and Tourism to Improve the Skills of Training Participants in the Hospitality Sector - Nugraha, Surya; Budiasa, I Ketut (Akademi Komunitas MAPINDO, 2023)
This research is motivated by the importance of training, to improve skills and develop competitive andcompetent human resources (HR). UPTD BLK Bali Industry and Tourism has a training program in thehospitality sector which will produce a competent workforce. The focus of research in writing this thesis are:(1). What is the role of the implementation of training to improve the skills of trainees at UPTD BLK for BaliIndustry and Tourism Job Training (2). How the training facilities are used for the training process (3). What isthe impact of training at UPTD BLK Bali Industry and Tourism (4). How UPTD BLK Bali Industry and Tourismfacilitates training participants. In this research, the research method uses descriptive qualitative data methodby taking primary data sources directly obtained in the field and secondary data obtained from documents inthe form of brochures and photographs. And data collection techniques by means of interviews, documentationand observation. The results of this study indicate that the role of UPTD BLK in the implementation ofhospitality skills training is as a provider of funds, programs, instructors, materials, teaching methods andtraining participants supported by supporting theoretical and practical facilities, although there needs to beimprovements in classroom facilities. The impact of this training is very good with the increase in the skills ofthe participants, so that it can increase the family economy, participants can create a home industry. As well assupport from the Bali Industry and Tourism UPTD BLK to facilitate participants by including in the SISNAKERsystem as a bridge between participants and industry (employers).Keywords: Role of UPTD BLK, impact of training, competent and competitive workforce